Fiberglass Boat Repair Training on Meosbekwan Island, Ayau Islands, Raja Ampat - Rezza Ruzuqi; Muh. Akhsan Samaila; Irman Amri; Arief Nasrul Firdani; Safriansyah Safriansyah (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Meosbekwan Island is one of the outermost islands of Indonesia which is administratively located in the Raja Ampat district. Generally, the Meosbekwan people work as fishermen who use boats less than 12 meters in size as the main means of transportation. Most ships are made of Fiber-reinforced plastic (FRP) or Fiberglass-reinforced Polymer Composite Materials. The condition of the area, surrounded by coral reefs, so that many ships were damaged because they hit the reef. The ship repair process is very difficult, because the condition of the area is far from urban areas. In general, the ship repair process adjusts to the level of damage. On the island of Meosbekwan, the ship's damage to the lower hull was torn and porous. The use of appropriate repair standards, needs to be applied so that the ship provides a sense of security and comfort for users. The procedure for repairing a damaged fiberglass boat consists of removing the outer layer until a solid part is found, then filling the damaged part with a resin-catalyst alloy reinforced with fiberglass Woven Roven 600 and Chopped Strand Mat 450. The number and variety of layers are adjusted by reference. The repair method used is the Hand Lay Up method. During the activity, one of the boats was completed together with the fishing community of Meosbekwan Island.